1997
DOI: 10.1007/s001250050801
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of proteolysis and de novo synthesis to alanine production in diabetic rat skeletal muscle: a 15 N/ 1 H nuclear magnetic resonance study

Abstract: Although glutamine has recently emerged as a major source of new carbon for gluconeogenesis, alanine is still considered to be an important glucose precursor in humans [1][2][3][4]. The mechanisms of altered alanine turnover rates during diabetes, however, are not completely understood. Alanine release is increased from rat muscle in experimental diabetes [5][6][7] and the interorgan flux of this amino acid is slightly elevated in spite of decreased plasma alanine in diabetic humans [8,9]. From these data, ske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…No statistically important differences between normoglycaemic women and those with GDM were reported for ILE and LEU, only VAL results were significant (p=0.01). Meynial-Denis et al [37] showed an increased level of LEU transformation into ALA in skeletal muscle in diabetes. They also observed an increase in ALA concentration, as well as an increased rate of metabolism of these amino acids.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…No statistically important differences between normoglycaemic women and those with GDM were reported for ILE and LEU, only VAL results were significant (p=0.01). Meynial-Denis et al [37] showed an increased level of LEU transformation into ALA in skeletal muscle in diabetes. They also observed an increase in ALA concentration, as well as an increased rate of metabolism of these amino acids.…”
Section: Discussionmentioning
confidence: 98%
“…Freyse et al [36] and Meynial-Denis et al [37] report higher levels of ALA in animals with diabetes. This level is not confirmed by the current research.…”
Section: Discussionmentioning
confidence: 99%
“…Also in the liver, we saw a decreased hepatic conversion of pyruvate to alanine, potentially indicating an increased supply of alanine from outside the liver due to insulin resistance. [21][22][23] The data could be representative of a change in the relative flux through the exchange reaction mediated by ALT, decreasing the incorporation of the 13 C label from pyruvate into the hepatic pool of alanine.…”
Section: Diabetic Studymentioning
confidence: 98%
“…More extensive studies in MRS have been conducted with a number of tracer molecules permitting the analysis of the intracellular milieu, metabolite kinetics, drug distribution and metabolism, ion fluxes, and metabolite dynamics. These nuclides used as tracers in MRS include l33 Cs (Schornack et al 1997), 2 H (Eng et al 1990), 15 N (Kanamori andRoss 1997;Meynial-Denis et al 1997), 17 O (Arai et al 1990Fiat et al 1992;Ronen et al 1998;Sibson et al 1998), 13 C (Bhujwalla et al 1994;Pascual et al 1998;Peled-Kamar et al 1998;Sibson et al 1998), 87 Rb (Cross et al 1995;Deslauriers and Kupriyanov 1998;Syme et al 1990), and 19 F (Hees and Sotak 1993;Mason et al 1993;McSheehy et al 1997).…”
Section: Magnetic Resonance Imaging (Mri) and Spectroscopy (Mrs 1 )mentioning
confidence: 98%